Legal Reconstruction of Customary Land Rights under Mortgage Law - Septhian Eka Adiyatma; Uche Nnawulezi (Universitas Semarang, 2026)
This study examines legal uncertainty in using customary land as collateral within Indonesia’s mortgage system. Legal pluralism under Basic Agrarian Law 1960 creates tension between customary tenure and the formal registration regime required by Law Number 4 of 1996 concerning Mortgage Rights. The study aims to assess whether customary land can meet the principles of publicity and speciality and to formulate a reconstruction model accommodating both systems. Using a normative juridical method with statutory, conceptual, and comparative approaches, the research analyzes legislation, doctrine, and case studies involving collateral disputes. Findings indicate that customary land, being communal and unregistered, cannot directly satisfy publicity and speciality due to lack of registration and unclear ownership boundaries, resulting in legal uncertainty for creditors, particularly regarding enforceability and priority rights. Nevertheless, adaptive reconstruction is possible through partial formalization, including recognition of communal rights within land administration and establishment of collective legal subjects representing indigenous communities. Comparative analysis with Rwanda shows that full formalization increases economic utility but risks eroding communal values. This study introduces the concepts of collective speciality and quasi-publicity as a hybrid framework bridging customary and formal systems, enabling customary land to function as collateral while preserving its communal character and ensuring balanced legal certainty and socio-cultural protection. AbstrakPenelitian ini mengkaji ketidakpastian hukum dalam penggunaan tanah adat sebagai objek jaminan dalam sistem hak tanggungan di Indonesia. Pluralisme hukum dalam Undang-Undang Pokok Agraria 1960 menimbulkan ketegangan antara rezim tanah adat dan sistem pendaftaran formal yang disyaratkan oleh Undang-Undang Nomor 4 Tahun 1996 tentang Hak Tanggungan. Penelitian ini bertujuan menganalisis apakah tanah adat dapat memenuhi prinsip publisitas dan spesialitas serta merumuskan model rekonstruksi hukum yang mengakomodasi kedua sistem. Metode yang digunakan adalah yuridis normatif dengan pendekatan peraturan perundang-undangan, konseptual, dan komparatif, melalui analisis doktrin, regulasi, dan studi kasus. Hasil penelitian menunjukkan bahwa tanah adat yang bersifat komunal dan tidak terdaftar belum dapat memenuhi prinsip publisitas dan spesialitas akibat ketiadaan pendaftaran serta ketidakjelasan batas dan subjek hak, sehingga menimbulkan ketidakpastian hukum bagi kreditor, khususnya terkait eksekusi dan hak preferen. Namun demikian, rekonstruksi hukum adaptif dimungkinkan melalui formalisasi terbatas, pengakuan hak komunal dalam administrasi pertanahan, serta pembentukan subjek hukum kolektif masyarakat adat. Perbandingan dengan Rwanda menunjukkan bahwa formalisasi penuh meningkatkan fungsi ekonomi tanah, tetapi berisiko menggerus nilai komunal. Kebaruan penelitian ini terletak pada konsep spesialitas kolektif dan quasi-publisitas sebagai kerangka hibrid yang memungkinkan tanah adat berfungsi sebagai jaminan tanpa menghilangkan karakter komunalnya.